Compartmentalization and the role of polyphony in moral dialogue - Turunen, Taija (Journal of business ethics, 2025)
Existing research on identity compartmentalization highlights concerns about moral (ir)responsibility arising from the incomplete integration of multiple role identities necessary for exercising full moral agency. Our study examines the (non)recognition of otherness by managers in morally ambiguous situations during industry-level changes. We adopt a dialogue-based approach, inspired by Bakhtin, and Ricoeur, to analyze compartmentalization from the perspective of polyphonic dialogue. Through an analysis of 61 interviews across four distinct change contexts, we identify five dialogue dynamics that either hinder or facilitate the recognition of alternative moral perspectives, shaping the formation of moral polyphony. We contribute to current understandings of compartmentalization by emphasizing its dialogical and fluid nature, the generative potential of division, and the role of conflicting moral convictions in change situations, as an ideal context for fostering moral polyphony.